SAT0453 Association of comorbid pulmonary conditions with patient-reported outcomes in systemic lupus erythematosus. (12th June 2018) - Katz, P.; Pedro, S.; Alemao, E.; Mukherjee, J.; Michaud, K.
Abstract : Background: Risk of chronic obstructive pulmonary disease (COPD) and allergic conditions, including asthma (AM), is elevated among SLE patients. 1 Both AM and COPD negatively affect quality of life measured through patient-reported outcomes (PROs). Little research has examined the impact of AM and COPD on PROs in SLE, independent of SLE disease status. Objectives: Determine the impact of AM/COPD on PROs in SLE, concurrently and longitudinally. Methods: Data from 2 large, longitudinal, observational cohorts were examined (Lupus Outcomes Study, LOS: n=796; National Data Bank for Rheumatic Diseases, Forward: n=2804). AM and COPD were determined at study entry by self-report. PROs included validated scales or items measuring physical functioning, fatigue, pain, cognitive function, depressive symptoms and global severity, although the cohorts included different PROs (Table). Multiple regression analyses examined differences between subjects with and without AM/COPD cross-sectionally, controlling for age, sex, race, lupus duration, education, income, obesity, smoking, other comorbid conditions, and presence or history of renal involvement, clotting disorder or seizures. Longitudinal analyses examined PROs at 3 years (yrs) of follow-up, controlling for covariates above as well as baseline PRO values. Results: LOS cohort was 92% female, mean age 47 years, 70% white, 42% ever smokers, mean lupus duration 13 years. Forward cohort was 94% female, mean age 51 years, 87% white, 38% ever smokers, mean lupus duration 16 years. 36% of LOS and 30% of Forward reported AM/COPD at study entry, compared to COPD prevalence of 7% 2 and AM prevalence of 9.7% 3 among US women. In cross-sectional analyses (Table), AM/COPD were associated with significantly worse scores on all PRO measures, except depressive symptoms (LOS). Longitudinal results were similar: AM/COPD were associated with worse scores on all PROs except SF-36 PF and Fatigue in LOS. Conclusions: AM/COPD are more common in SLE than the general population and are independently associated with worse outcomes on a wide range of PROs, even after controlling for sociodemographic and lupus characteristics. Findings suggest that physicians should screen for pulmonary comorbidities and ensure adequate treatment for these conditions. Future analyses of PROs in SLE should include AM/COPD as important comorbid conditions. References: [1] Shen T-C, et al. PLoS One2014;9:e91821. [2] Ford ES, et al. Chest2013;144:284–305. [3] www.cdc.gov/asthma/most_recent_data.htm. Last accessed 4 January 2018. Disclosure of Interest: P. Katz Grant/research support from: Bristol-Myers Squibb, S. Pedro Grant/research support from: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Mukherjee Employee of: Bristol-Myers Squibb, K. Michaud Grant/research support from: Pfizer and Rheumatology Research Foundation, Employee of: University of Nebraska Medical Centre and National Data Bank for Rheumatic Diseases